Effects of dictogloss on non-english majored undergraduates’ listening comprehension - Hai, Ngo Thi Minh (H. : ĐHQGHN, 2020)
Listening has long been considered a hard-to-deal skill for both ESL teachers and learners. Although there are abundant studies on this field aiming to diversify in-class listening activities and make them more efficient for learners, the demand for one which manages to provide or reinforce necessary linguistic knowledge for students is still high. This action research was conducted with 40 pre-intermediate non-English majored students through three qualitative methods including focus group interview, teacher’s diary and artifacts to examine the effects of dictogloss on listening comprehension in English teaching and learning process and to explore the learners’ attitudes towards this practice. Findings of the study were that dictogloss helped to improve the learners’ listening comprehension through activating and raising their awareness of linguistic knowledge and providing them a clear context for listening, which also made them more interested in the activity.